(untitled)
In this paper, the dual mixed method for an unilateral problem, which is the simplified modelling of scalar function for the friction-free contact problem, is considered. The dual mixed problem is introduced, the existence and uniqueness of the solution of the problem are presented, and error bounds O(h^34 ) and O(h^32 ) are obtained for the dual mixed finite element approximations of Raviart-Thomas elements for k=0 and k=1 respectively. , number=6, journal=Journal of Computational Mathematics, year=2021, month=July, pages=733–746